A model for integrating energy management in lean production - Javied, Tallal; Deutsch, Marius; Franke, Jörg (Procedia CIRP, 2019)
The implementation of sustainable production systems has been the focus of political, economic and social efforts for years. Due to the switch from fossil fuels to green energies, energy costs have been rising steadily for years. Energy-related taxes and levies can be reduced with a certified energy or environmental management system. ISO 50001 specifies requirements for the implementation of energy management system. Nevertheless, since 2017, ISO 50003 requires companies to demonstrate, by means of indicators, that energy efficiency is actually being continuously improved. Until now, only the proof, which shows that a systematic approach to reduce energy consumption is employed, was sufficient as a basis. However, the focus has now shifted towards the optimization of energy management systems. Nonetheless, these norms allow a wide scope for interpretation. This paper contains a methodology for the implementation of energy management system according to which companies can design there structure and processes to fulfil all the requirements specified in ISO 50001 and the other relevant energy management standards. The technical, business and organizational possibilities as well as the involvement of personnel along the McKinsey 7S model are considered. McKinsey's 7S change management tool provides the framework. The sustainable success of companies is analyzed using hard and soft factors. In this case, the model is applied to management systems.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Energy management; ISO 50001; Process design

A multi-physics simulation approach for energy and cost analysis during the deceleration of high-speed trains - Meinel, David; Javied, Tallal; Rast, Sebastian; Zipp, Christian; Franke, Jörg (Procedia Manufacturing, 2018)
The kinetic energy of cruising high-speed trains is significant and should be saved if possible. On the one hand, regenerative braking only goes along with a low deceleration rate due to the limited motor power and needs to be compensated with energy-wasting high travelling speeds in order to travel within a given schedule. On the other hand, travelling with lower speeds demands for adding wear-prone mechanical braking power to keep the speed up long enough. This dilemma makes for the scientific quest of this paper to examine these two opposing approaches using a multi-physics train model for simulations featuring distributed brake and motor models across the train model. The simulation scenarios herein are characterized by different ratios of disc braking forces and regenerative braking forces. Plainly electric braking turned out the most economical but less effective than adding mechanic braking force. A compromise strategy for both making for schedule buffers and achieve a satisfying efficiency has been found. Engaging the mechanic disc brakes turned out to be indispensable for avoiding schedule delays. A study about reinforcing the motor equipment to increase the braking capacity resulted in a potential improvement of the economic efficiency during the life cycle of trainsets.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy; high-speed; management; mechatronic; model; Modelica; multi-physics; simulation; train; train

A standby strategy model for an energy efficient soldering oven machine - Esfandyari, Alireza; Javied, Tallal; Reissmann, Felix; Franke, Jörg (2016 IEEE Conference on Technologies for Sustainability, SusTech 2016, 2017)
The convection based soldering technologies in electronics assembly consume massive electrical energy. The recent advancements in soldering technologies consume comparatively higher resources and need to be optimized for resource efficient production which is also the motivation for the present work. This paper has an energy consumption reduction perspective by considering a detailed analysis of operation and system component interactions with respect to various use phase regimes of the reflow oven in electronics manufacturing. The methodology derives a detailed analysis and monitoring of all electrical energy intensive components of the oven. The soldering process phase requires a state based modification of electrical energy consumption for non-productive process times. An optimization model enables to define the optimal state within a given waiting time window on energy-minimal operating state trajectories in the oven. Using the modelling framework, a strategic decision making processes that make it possible to exploit the potential for energy consumption minimization of any non-productive times is introduced.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Electronics production; energy efficiency; soldering oven; standby mode

Cloud based Energy Management System Compatible with the Industry 4.0 Requirements - Javied, Tallal; Huprich, Sven; Franke, Jörg (IFAC PAPERSONLINE, 2019)
CRIS-Team WoS Importer:2019-11-22

Demand-based dimensioning of compressed air systems for energy optimization and flexibility - Javied, Tallal; Kimmig, Florian; Franke, Jörg (Proceedings - 2018 4th International Conference on Control, Automation and Robotics, ICCAR 2018, 2018)
Due to high energy prices in Germany, manufacturing companies have an incentive to increase energy efficiency in production. Compressed air systems (CAS) offer high energy savings potentials. Studies show that CAS are poorly dimensioned in most cases. This paper describes the energy saving potential of compressed air systems. Additionally the importance of not only energy efficiency but energy flexibility is considered. To optimize the current systems and to determine need-based determination of CAS, a Software-tool was developed based on visual basic for application and MS Access. This tool is described in this paper. Different studies estimate a savings potentials due to efficient dimensioning at more than 15%. The described tool helps users identify their energy saving and flexibility potential and suggests CAS configuration to utilize the given potential. It illustrates different investment scenarios based on user-specific requirements. Users can evaluate alternatives that suit their needs based on different KPIs. This tool is designed for SMEs in order to allow them to analyze their CAS without requiring costly external consultation. Energy flexible CAS can enable users to Buy energy at lower costs and use it when prices are high. A smart factory can manage these control challenges independently and utilize the form of energy which is situationally most favorable. Thereby, both economical advantage and energy flexibility can be ensured.
CRIS-Team Scopus Importer:2023-03-07
Keywords: component; compressed air system; energy efficieny; energy flexibility

Energy controlling - Analysis and evaluation of energy measuring equipment for the purpose of energy transparency in production plants - Rackow, Tobias; Javied, Tallal; Geith, Teresa; Schuderer, Peter; Franke, Jörg (Applied Mechanics and Materials, 2014)
This paper addresses the analysis and evaluation of energy measuring devices for the operation in the manufacturing industry. The focus lies on the comparison and scoring of energy meters regarding their performance spectrum against the backdrop of an energy controlling. Based on the fundamentals of electro technical metrology, the main measurement parameters were identified which are necessary for the purpose in the manufacturing industry. Further, capability characteristics for the differentiation of electricity meters were defined. With this, a classification of meters into a basic, a standard, an advanced and a premium class was undertaken. It is shown, that the advanced class is sufficient for the permanent monitoring of electricity consumption in the lights of energy controlling.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy controlling; Energy efficiency; Energy measuring equipment

Energy efficiency investigation on high-pressure convection reflow soldering in electronics production - Esfandyari, Alireza; Syed Khaja, Aarief Hussain; Javied, Tallal; Franke, Jörg (Trans Tech Publications Ltd, 2014)
One of the key factors in efficient and defect-free electronics manufacturing is the soldering of electronic components to the printed circuit boards. The deciding factor in the reliability and lifetime of the product is the quality of the soldered interconnections. The setting up of the reflow soldering profile plays a crucial role in the electrical functionality and robustness of the product. Especially the miniaturization of the assemblies and the development of new materials make it inevitable for the definition of new processes, optimization and implementation. In this paper, the combination of over-pressure and convection reflow soldering to minimize the defect rate and the related energy analysis for energy efficiency will be discussed and presented. An analysis with variations in solder time, cost, energy, quality trade-off in the over-pressure reflow soldering process for classical printed circuit boards (PCBs) has been demonstrated.
Keywords: Convection reflow soldering; Electronics production; Energy efficiency; Over-pressure

Green cockpit: Transparency on energy consumption in manufacturing companies - Rackow, Tobias; Javied, Tallal; Donhauser, Toni; Martin, Andreas; Schuderer, Peter; Franke, Jörg (12th Global Conference on Sustainable Manufacturing, GCSM 2014, 2015)
Companies are forced by rising energy costs to seize control of their energy consumption to maintain contestability. Therefore, transparency over the companies' energy flux along the production process is required. Energy data management software is helpful, but cost-intensive. Hence, especially small and medium sized enterprises (SME) spare this investment. In this paper, the requirements for an energy controlling infrastructure in SME are elaborated, followed by a deduced software-architecture which supports the respective controlling structure. Further, the prototypical realization of the corresponding tool "Green-Cockpit" will be presented. The free of cost, open source and web-based tool is designed to help companies monitor, interpret, analyze, plan and report their energy consumption. The Green Cockpit tool outperforms other energy management software at management disciplines with its ability to not only analyze energy consumption, but plan and control it additionally.
Keywords: Energy controlling; Energy management; Open source data management; Operations management

Identification of energy consumption and energy saving potentials of electric drive systems - Javied, Tallal; Kreitlein, Sven; Esfandyari, Alireza; Franke, Jörg (Applied Mechanics and Materials, 2014)
This paper provides an overview of different types of motor systems and several measurement principals in order to determine the electricity usage of these motors. It focuses on the measurement of electric values of different drive systems. A concept of rough analysis using software or excel based tools is discussed, which argues that it is a lot easier, efficient, and cost effective to first pin point the main electricity consumers and then initiate a fine analysis of these selected systems before a cost and time intensive process of measuring every single drive system is undertaken. To achieve this, a simple and systematic process is illustrated in this paper, which can be used to identify the energy saving potential of drive systems without requiring expensive hardware.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy efficiency; Energy management; Energy measurement

Implementing energy management system to increase energy efficiency in manufacturing companies - Javied, Tallal; Rackow, Tobias; Franke, Jörg (Procedia CIRP, 2015)
One of the main pillars of the modern industry is the uninterrupted supply of energy with a reasonable price. The energy production is based mostly on non-renewable energy resources that are getting more expensive progressively. This increase in energy cost consequently leads the companies to a more expensive production of goods. Therefore it has been established that energy efficiency is not only very important for the environment but also for the sustainable production in the manufacturing companies. Effective energy management plays an important role in the necessary increase of energy efficiency in industry. Next to the expansion of regenerative energies, it establishes a further pillar at closing the energy supply gap resulting from the energy transition. This paper presents the current energy situation in Germany and its impact on the German industry. Furthermore this paper presents a methodology which can be used by organizations to systematically implement energy management system. Eventually the paper provides a model that illustrates the realization of a PDCA cycle which is necessary for energy management in the organization.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy efficiency; Energy management; Organization structure; Sustainability

Intelligente Versorgungssysteme für Druckluft und technische Gase - Böhm, Ralf; Javied, Tallal; Franke, Jörg (Industrie 4.0 Management : Gegenwart und Zukunft industrieller Geschäftsprozesse, 2017)

Multi-Objective Design Space Exploration for the Integration of Advanced Analytics in Cyber-Physical Production Systems - Bakakeu, Jupiter; Fuchs, Jonathan; Javied, Tallal; Brossog, Matthias; Franke, Jörg; Klos, H.; Eberlein, W.; Tolksdorf, S.; Peschke, J.; Jahn, L. (2018 IEEE INTERNATIONAL CONFERENCE ON INDUSTRIAL ENGINEERING AND ENGINEERING MANAGEMENT (IEEE IEEM), 2018)
CRIS-Team WoS Importer:2019-02-27

Planning, evaluation and comparison of electric drive systems using various configurations to increase energy efficiency and optimize alternating current drive systems - Javied, Tallal; Menk, Jochen; Franke, Jörg (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2015)
The industrial sector is the largest consumer of produced electric energy worldwide. Electric motor systems account for about 70 percent of the total industrial electricity demand and possess a great cost and energy saving potential. The paper provides an overview of global and regional efforts to create awareness for potential cost drivers in the industry. Various software and excel-based tools for a preliminary estimation of the energy consumption of electric motor systems are available in the market, but a holistic approach is missing. Therefore a framework and a systematic process for the estimation of potential energy savings in motor systems running on alternating current are illustrated in this paper. Moreover a new software tool is discussed, that allows a holistic view on all motor systems within a company without cost-intensive measurements or the use of external consultants.
CRIS-Team Scopus Importer:2023-03-07

Strategic energy management in industry 4.0 environment - Javied, Tallal; Bakakeu, Jupiter; Gessinger, Dennis; Franke, Jörg (12th Annual IEEE International Systems Conference, SysCon 2018 - Proceedings, 2018)
One of the latest innovations in the industrial environment was the emergence of Industry 4.0. Along with numerous challenges, there are many chances for companies in it. Besides automation, energy efficiency and energy flexibility is becoming increasing important. Because of the planned phasing-out of nuclear power and high prices for energy, it is important for companies to reduce their energy consumption in order to reduce cost and stay compatible in market place. Therefore strategic energy management plays an important role in overcoming these obstacles. Implementation of energy management is often based on standards and norms with the DIN EN ISO 50001 being the most important. Energy monitoring is a key factor for the successful execution of energy management. For energy monitoring of Industry 4.0 production plants, a cloud based energy monitoring and management system was developed. This solution allows users to monitor their production in real time enabling them a possibility of condition monitoring, energy flexible planning of production based on historic data and energy management along with load management. The detailed concept of the cloud based totally integrated energy management system, beginning with data acquisition to data analysis and visualization is presented in this paper.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy management; Energy monitoring; Industry 4.0

Systematic energy management: A foundation for sustainable production - Javied, Tallal; Esfandyari, Alireza; Franke, Jörg (2016 IEEE Conference on Technologies for Sustainability, SusTech 2016, 2017)
In the past few years energy management became increasing important. Not only the trend toward clean energy sources triggered a process of rethinking in the minds of society but also pushed the politics to create incentives for companies in order to make them reduce their carbon footprint. Efficient use of resources has become a fundamental part of present-day economic, social and political decision making. Energy efficient production is no longer considered just under ecological aspect. It is considered as an important part of business strategy. Through high energy taxes, enormous energy costs and continuously increasing energy prices manufacturing companies are under permanent stress. However, there is for companies in the field of energy management enormous potential to financially improve and save costs consequently. Standards have provided a guide line for the companies to move towards green production. However lack of know-how and appropriate software tools and absence of concepts and methods for green production hinders company's especially small and medium size enterprises to take the step towards green production. Systematic and strategic energy management is the key to transform a company from lean to green production. Because of the complexity of the tasks related to environment and energy management, the Institute for Factory Automation and Production Systems (FAPS) developed methods and concepts to implement a strategic energy management. Furthermore, a software is developed that enables companies to follow the ISO 50001 guidelines and implement energy management methods necessary for a green production. This paper provides a brief road map showing the path to an energy efficient production environment. Starting from the list of the main energy consuming applications in German industries, which were identified through a study carried out in 2015. Brief description of the energy management methods and concepts and illustration of the role of strategic energy management in transforming companies from lean to green production and finally a brief illustration of the software for the implementation of energy management especially in manufacturing companies.
CRIS-Team Scopus Importer:2023-03-07
Keywords: energy efficiency; energy management; sustainable production